Palaearctic osmiine bees of the genera Hofferia and Stenoheriades (Megachilidae, Osmiini): biology, taxonomy and key to species - Müller, Andreas; Trunz, Vincent (Zootaxa, 2014)
Hofferia and Stenoheriades are closely related, species-poor genera of the osmiine bees (Megachilidae). Analysis of female pollen loads and field observations indicate that species of both genera have a strong affinity to Asteraceae as pollen hosts. Both genera use insect burrows in dead wood as nesting site, and Hofferia schmiedeknechti was found to build cell walls and nest plug with resin partly mixed with small pebbles. The taxonomic revision of the Palaearctic Hofferia and Stenoheriades species revealed the existence of a still undescribed species in the Levant, Stenoheriades levantica spec. nov.. Stenoheriades hofferi (Tkalců, 1984) is synonymized with S. coelostoma (Benoist, 1935), which is distinct from S. asiatica (Friese, 1921), and Heriades integra Benoist, 1934, formerly considered a Stenoheriades species, is synonymized with Osmia (Hoplosmia) scutellaris Morawitz, 1868. Keys for the delimitation of Hofferia and Stenoheriades from the other Palaearctic osmiine bee genera and for the identification of the Palaearctic species are given.